2008
DOI: 10.1577/a07-046.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dissolved Oxygen Concentration on Oxygen Consumption and Development of Channel Catfish Eggs and Fry: Implications for Hatchery Management

Abstract: Eight channel catfish Ictalurus punctatus spawns were split into two similar portions and incubated under controlled conditions to determine the effect of dissolved oxygen (DO) concentration on the development and survival of eggs and fry. The DO concentration was 7.42 ± 0.03 mg/L (mean ± SD; 92.5% saturation) and 18.40 ± 0.28 mg/L (230% saturation) through hatching in the low‐ and high‐oxygen treatments, respectively. Eggs hatched 6 h earlier in the low‐oxygen treatment, but fry reached swim‐up stage 31 h lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Prematurely hatched fry were present in each treatment and comprised less than 1% of the total hatch; data indicated that PMH fry were arbitrarily distributed among all treatments. Torrens and Steeby (2008) suggested that low DO on the last day of incubation may account for PMH fry, and those authors found that it takes longer for these fry to reach the swim-up stage in comparison with normal fry; fry in the present study were euthanized when hatching was complete and before the swim-up stage. Straus et al (2009b) described the elimination rates of CuSO 4 from this system and the reasons for choosing the 0.22-µm nylon filter pore size and for obtaining the water sample 30 s after the treatment was applied.…”
Section: Resultsmentioning
confidence: 53%
“…Prematurely hatched fry were present in each treatment and comprised less than 1% of the total hatch; data indicated that PMH fry were arbitrarily distributed among all treatments. Torrens and Steeby (2008) suggested that low DO on the last day of incubation may account for PMH fry, and those authors found that it takes longer for these fry to reach the swim-up stage in comparison with normal fry; fry in the present study were euthanized when hatching was complete and before the swim-up stage. Straus et al (2009b) described the elimination rates of CuSO 4 from this system and the reasons for choosing the 0.22-µm nylon filter pore size and for obtaining the water sample 30 s after the treatment was applied.…”
Section: Resultsmentioning
confidence: 53%
“…We found survival to swim-up stage from the trough with the lowest DO concentration to be 80.9%, only 4% below the study average of 84.9% and slightly higher than the industry average of 79.3%. Our results suggest the vertical-lift incubator provides superior water (and oxygen) movement through the egg masses, and thus achieved a higher internal DO concentration in the egg masses than did Torrans and Steeby (2008) with a lower external DO concentration. However, the effect of the new incubator design on the water circulation and oxygen delivery to the center of the egg masses, which is the presumptive factor limiting egg-mass loading densities in traditional paddle-type incubators, was not directly determined.…”
Section: Resultsmentioning
confidence: 73%
“…Nitrite-N in all troughs tested was below detectable levels. Torrans and Steeby (2008) split channel catfish egg masses in half and incubated each in a separate tank using forced-air agitation. They observed premature hatching and a 16.4% poorer survival to swim-up stage with eggs incubated in water with a DO concentration of 92.5% air saturation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both SCP and hydrogen peroxide increased dissolved oxygen in the hatching troughs. This is a beneficial effect because DO concentrations above 7.4 mg/L at 268C have been shown to improve channel catfish hatching success (Torrans and Steeby 2008). The greatest effect of SCP on water quality appeared to be pH.…”
Section: Discussionmentioning
confidence: 98%